Accounting and management control practices in the automotive sector - Gomes, Isabel (2020)
This work aims to identify the main management control tools used by multinational companies in the automotive operating in Portugal and to identify the motivations that supported the decision to implement these tools.The New Institutional Sociology (NIS) provides the appropriate theoretical framework to explain the motivations of managers in choosing the accounting model and management control in organizations. This work adopts an interpretive paradigm and applies the methodology of multiple case studies, comparatively analysing four organizations in the automotive sector. The data were collected from multiple sources, namely semi-structured interviews, documents and direct observation. The results suggest the existence of isomorphic practices of accounting and management control. However, longitudinal studies will be needed to understand how and why these isomorphism processes occur.